Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Air Mineral Nestle Pure Life Dimediasi Oleh Kepuasan Konsumen di Yogyakarta - ningrum, erlina septiya (Politeknik Bisnis Indonesia, 2024)
The mineral water industry in Indonesia continues to grow with increasing public awareness of the importance of health and a healthy lifestyle. Mineral water products are no longer considered a luxury item, but rather a basic necessity that must be available every day. With increasingly fierce competition between brands, consumers' decision to purchase a product depends on several key factors, such as price, product quality, and satisfaction. The study intends to determine the influence of price and product quality on purchasing decisions, using the mediation of consumer satisfaction. This study uses a quantitative research method, this research sample is people who have bought pure life mineral water in Yogyakarta with a sample number of 123. This research was tested using SEM-PLS. The results of this research are: 1) There is no positive and significant influence of Price on Consumer Satisfaction.2) There is a significant direct influence of product quality on consumer satisfaction. 3) There is no positive and significant influence of Price, on the decision to purchase the product. 4) There is no positive and significant influence of Product Quality on Purchase Decisions. 5) There is a significant direct influence of Consumer Satisfaction on Purchase Decisions. 6) There is no positive and significant influence of Price on Purchase Decisions mediated by the Consumer Library. 7) There is a significant direct influence of Product Quality on Purchase Decisions mediated by Consumer Satisfaction).